Active control of contact force for high-speed railway pantograph-catenary based on multi-body pantograph model. (September 2017) - Song, Yang; Ouyang, Huajiang; Liu, Zhigang; Mei, Guiming; Wang, Hongrui; Lu, Xiaobing
Abstract: Active control of pantograph is a promising approach in improving the current collection quality of high-speed railway pantograph-catenary system. To address the shortcomings of the lumped-parameter pantograph model used in previous studies, a multi-body model of pantograph is established, and two configurations of installing actuators on a multi-body pantograph are presented. In combination with a nonlinear finite element model of catenary, the control performance is evaluated through several numerical simulations. First of all, the effect of control gains on the control performance is analyzed. Then considering more realistic conditions, the controller time-delay and the limitation of controller sensitivity are included, whose influence on the control performance is investigated. At last, considering realistic external disturbance (strong wind load and locomotive vibration) to pantograph-catenary system the control performance is evaluated in decreasing the fluctuation in contact force as well as eliminating the contact loss. The results indicate that the proposed controller with larger control gains has better performance in decreasing the fluctuation of the contact force between the multi-body pantograph and the nonlinear finite element catenary, but has lower robustness against the controller time-delay. The reduction of controller sensitivity results in a fluctuating degradation of the control performance.